Al-Qur'an Learning with the Yanbu'a Model for the Quality of Pronunciation of Hijaiyah Letters at Islamic Boarding Schools - Sylvia Candra Devi; Dzulfikar Akbar Romadlon (Adabiyah: Jurnal Pendidikan Islam, 2023)
This study aims to determine the learning of the Koran with the yanbu'a model for the quality of the pronunciation of hijaiyah letters at the Ar-Roudhoh Krian Sidoarjo Islamic Boarding School and to find out the supporting and inhibiting factors in its application. The research method used is descriptive qualitative which produces data in the form of written words from the results of interviews, observations and documentation. The results showed that: (1) The application of the Yanbu'a model used 3 classical models, sorogan, and tadarus. Although the learning of the Qur'an was carried out well, phonological errors were found in the pronunciation of the hijaiyah letters, namely consonant errors and vowel errors. (2) The supporting factors are in practice using many variations and supported by khataman activities and giving awards to students who have achieved the memorization target. While the inhibiting factor is the application of existing regulations during the learning process of the Al-Qur'an pronunciation of the hijaiyah letters that are not enforced to students, especially the inadequate facilities and infrastructure so that the yanbu'a model for the quality of the pronunciation of the hijaiyah letters is less than optimal.